2015
DOI: 10.1111/jan.12649
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric systematic review of self‐report instruments to identify anxiety in pregnancy

Abstract: Many instruments have been adapted for use in different populations to those for which they were designed. The State Trait Anxiety Inventory, Edinburgh Postnatal Depression Scale and the Hospital Anxiety and Depression Scale have been tested more frequently than other instruments, yet require further assessment to confirm their value for use in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 79 publications
(192 reference statements)
1
44
0
2
Order By: Relevance
“…This region was named Bsmartest area of the world^in 2011 by the international think-tank Intelligent Community Forum (ICF) in New York. Pregnancy-specific distress instruments, such as the TPDS, the Cambridge Worry Scale (Green et al 2003), and the Prenatal Distress Questionnaire (Yali & Lobel 1999), were recently reviewed, concluding that further psychometric evaluation of existing pregnancy-specific scales was needed (Evans et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region was named Bsmartest area of the world^in 2011 by the international think-tank Intelligent Community Forum (ICF) in New York. Pregnancy-specific distress instruments, such as the TPDS, the Cambridge Worry Scale (Green et al 2003), and the Prenatal Distress Questionnaire (Yali & Lobel 1999), were recently reviewed, concluding that further psychometric evaluation of existing pregnancy-specific scales was needed (Evans et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since its development, the TPDS has been translated into English, Portuguese, Turkish, Spanish, and Bahasa Indonesia (e.g., apik & Pasinlioglu 2015). Morrell et al (2013) emphasized the fact that the TPDS was developed using focus-group interviews as a starting point, and a recent systematic review of self-report questionnaires of anxiety during pregnancy evaluated the TPDS as excellent in terms of its internal consistency and structural validity (Evans et al 2015). However, it was also concluded that data on hypothesis testing and construct validity was insufficient and data on reliability were not reported (Evans et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Measures were selected for their psychometric properties and because they possess good sensitivity and specificity (Beck, Epstein, Brown, & Steer, 1988;Blanchard, Jones-alexander, Buckley, & Forneris, 1996;Connor et al, 2000;Cooper & Murray, 1998;Cox, Holden, & Sagovsky, 1987;Eberhard-gran, Eskild, Tambs, Opjordsmoen, & Samuelsen, 2001;Foa et al, 2002;Kleinknecht & Thorndike, 1990;Klorman, Weerts, Hastings, Melamed, & Lang, 1974;Meyer, Miller, Metzger R.L., Borkovec, 1990;Molina & Borkovec, 1994;The PTSD Checklist, 1993). All screening tool, with the exception of the Specific Phobia Questionnaire (see below), have been validated in settings similar to our own (Chambless, et al, 2011;Connor et al, 2000;Eberhard-gran et al, 2001;Evans, Spiby, & Morrell, 2015;Foa et al, 2002;McDonald & Calhoun, 2010;Newman, Holmes, Zuellig, Kachin, & Behar, 2006;Simpson, Glazer M, Michalski, Steiner, & Frey, 2014;Walker, Newman, Dobie, Ciechanowski, & Katon, 2002). For most of the anxiety disorders, screening instruments which have been validated for use in perinatal populations do not exist.…”
Section: Self-report Measuresmentioning
confidence: 99%
“…Given the significant negative health impact of stress and anxiety on pregnant women and their offspring, access to effective anxiety- and stress-reduction treatments via easily-accessible and cost-effective therapies are crucial public health goals and are essential for improving the health and well-being of pregnant women and their children (Adler, Fink, Urech, Hösli, & Bitzer, 2011; Evans, Spiby, & Morrell, 2015). Although current best practices include the use of medication and long-term cognitive behavior therapy, alternatives to pharmaceutical treatments or resource-heavy psychological interventions are highly desirable to patients and health professionals alike and will increase the frequency and acceptability of such treatments during pregnancy (Bledsoe & Grote, 2006; Yonkers et al, 2009).…”
mentioning
confidence: 99%